INTRAPRENEURSHIP IMPACT ON GROWTH OF PRODUCTION COMPANIES IN BOSNIA AND HERZEGOVINA - Muzafer Brigić; Bahrija Umihanović (Ekonomski Vjesnik, 2015)
Growth and development are among the main goals of every company. A dedication to the activities which create conditions for growth and development is an important management operation. Entrepreneurial activity provides prerequisites so that growth and development can be achieved. In large and existing companies, entrepreneurial activity presents intrapreneurship. The subject of this paper is to what extent are intrapreneurial activities present in production companies in Bosnia and Herzegovina. In addition, we explored organizational prerequisites for intensifying the impact of intrapreneurship, and the impact of intrapreneurial activities on company growth. Primary research was conducted in the field using the survey as a tool for data collection. By interviewing people we obtained the answer to the question, to what extent is intrapreneurship developed in the production companies in Bosnia and Herzegovina in terms of two key dimensions of intrapreneurship: innovation and autonomy of action, and their impact on the growth of production companies. Additionally, we reached an answer as to what is necessary to do in the field of management of the companies in order to create assumptions for intensifying the intrapreneurial activities of those companies. The sample represented 50 major production companies in the Federation of Bosnia and Herzegovina. We used statistical methods of data processing: descriptive analysis, factor analysis, regression, and correlation. By analyzing the results of the research, we confirmed the hypothesis that the implementation of intrapreneurial activities has a positive effect on the development of production companies. Recommendations were given in order to improve organizational presumptions for intensive intrapreneurial activities.